Do Governance Mechanisms Matter? Evidence from Food and Beverage Sector in Indonesia - Hardi, Enny; Novriyandana, Rifqi; Miliya, Hisni; Junus, Amiruddin; Darmawati, Darmawati (Economics, Business, Accounting & Society Review, 2025)
This study investigates the impact of corporate governance mechanisms on financial performance, with a focus on publicly listed food and beverage manufacturing companies in Indonesia during the period 2017–2023. Grounded in Agency Theory, this research examines the influence of four key governance mechanisms: Independent Board of Commissioners (IBC), Audit Committee (AC), Managerial Ownership (MO), and Institutional Ownership (IO) on firm profitability as measured by Return on Assets (ROA). The study used multiple linear regression analysis. The results reveal that IBC, AC, and MO have statistically significant positive effects on ROA, confirming their roles as effective internal governance mechanisms in mitigating agency conflicts and promoting accountability. However, IO does not exhibit a significant relationship with financial performance, indicating that ownership by institutional investors alone may be insufficient to enhance firm value, particularly in emerging market contexts with weak regulatory environments and passive investment behavior. These findings underscore the necessity of context-sensitive governance reforms and suggest that ownership structures must be complemented by active monitoring and stakeholder alignment. Furthermore, the study highlights the limitations of single-theory approaches and advocates for a pluralistic governance framework that integrates multiple perspectives, including stewardship and stakeholder theories. By providing industry-specific insights and empirical evidence from an underexplored emerging economy sector, this study contributes to the evolving discourse on corporate governance effectiveness and offers practical implications for regulators, investors, and corporate leaders.